EMOTIONAL ASSOCIATIONS BETWEEN THE USER AND THE DESIGNED PRODUCT - ÜNAL , Bülent; GÜNEŞ , Elif (SSD Journal, 2021)
Today, consumption habits and behaviors have changed; consumption is no longer only within the scope of basic needs and basic use-value. People now consume not only the products they need, but also those they do not need. Although there are various products in the market, buying a specific product by choosing from among them may depend on the design features of that product. Due to these design features, an emotional relationship can be established between people and products, and people can buy products for this reason. In this context, it can be said that with the design decisions taken by the designer while designing a product, directly or indirectly, the product can be selected and purchased from among the options that are out of necessity. In this study, it is aimed to underline what these design features can be and the role of industrial designers at this point. In the result of the study, it is revealed that the emotional relationship is established with the design features of the products such as color, material, texture, form and usage, and the memories that people have accumulated in their lives with the help of these features.